(untitled) (Research, Society and Development, 2020)
The research of qualitative approach developed with the teachers of 4th and 5th years of the Municipal Secretary of Education in the municipality of Uruaçu-GO aimed to analyze the National Curriculum Guidelines (DCN) and the National Curriculum Parameters (PCN) of the Ministry of Education for the Science teaching and whether new technologies have been used in science classes at the school object of study. The work investigated whether the implementation of the DCN has contributed to the pedagogical practice of the teacher and to the teaching and learning process of students. The investigation is justified by the fact that the training and practice of teachers has been a target of concern. The research had as source of data collection: written records (documental analysis based on guiding questions); structured questionnaire and observation of classes. The questionnaire was intended to identify the subject’s profile, professional training, science conception, pedagogical actions and use of technologies. In addition to the aforementioned instruments, the researcher’s oral speeches (discursive interactions) with the participating teachers were used as field notes. The observations of the classes were carried out from May to October 2015 and made it possible to understand the pedagogical practice used. As a final product, two Didactic Sequences were elaborated as the theme: for the 4th year, Life cycle of human beings: being born, growing, reproducing, aging and dying; for the 5th year, the theme was Basic Sanitation: treated water. It is concluded that the results of this study allow teachers to stimulate the teaching of Sciences and contribute to the students to have greater learning.